EVALUASI PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN HIPERTENSI RAWAT INAP DI RUMAH SAKIT HERMINA SERPONG TAHUN 2019 - Suny Koswara Rahajeng; Setianti Haryani; Anis Dwi Kristiowati; Rachma Fitriana (PHRASE (Pharmaceutical Science) Journal, 2022)
The study aims to evaluate the use of antihypertensive drugs which include patient accuracy, indications, drugs, and doses in inpatients with hypertensive patients from January to December at Hermina Hospital in 2019 based on JNC 8 guidelines. This study is a descriptive study with retrospective data collection based on medical records. The sampling technique used is the total sampling technique. The results obtained from 78 samples based on patient characteristics for gender were 43 female patients (55,13%) and 35 male patients (44,87%). Characteristics of patients based on age obtained the most at the age of 45-≥65 years as many as 64 patients (82,05%). Characteristics of patients based on the pattern of drug use, the most widely used antihypertensive drug therapy was combination of ACEI + CCB as many as 47 patients (60, 26%). Evaluation of the use of antihypertensive drugs was obtained based on the right patient as many as 78 patients (100%), the right indication as many as 78 patients (100%), the right drug as many as 69 patients (88.46%), and the right dose as many as 69 patients (88.46% ).